AN IMPROVED MODEL FOR ATM IN A WIRELESS COMMUNICATION NETWORK USING QUEUING TECHNIQUE. (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Queuing is the common activity of customers or people to avail the desire service, which could be processed or distributed one at a time. Bank ATMs would avoid losing their customers due to a long wait on the line. The bank initially provides one or two ATMs in every branch. But, one or two ATMs not serve a purpose when customers withdraw to us ATM and try to use other bank atm. Thus the service time need to be improved to maintain the customers. This paper shows that the queuing theory used to solve this problem. We obtain the data from a bank ATM in the city. We then derive the arrival rate, service rate, utilization rate, waiting time in the queue and the average number of customers in the queue based on the data using little’s theorem and M/M/I queuing model. The arrival rate at a bank ATM on Monday during banking time is 1 customer per minute (CPM) while the service rate is 1.50CPM. The average number of customer in the ATM is 2 and the utilization period is 0.70. It was observed that queuing technique has great positive impact on customers in the bank by 0.5%